Penerapan Teknologi Budidaya Sayuran Ramah Lingkungan dengan Wadah Limbah Plastik di Kelurahan Tanjung Johor Kota Jambi - Eliyanti Eliyanti; Zulkarnain Zulkarnain; Budiyati Ichwan (PRIMA: Journal of Community Empowering and Services, 2022)
Application of Environmentally Friendly Vegetable Cultivation Technology with Plastic Waste Containers in Tanjung Johor Village, Jambi City. The Sekintang Dayo Farmer Group is is part of the community who live in Tanjung Johor Village, Pelayangan District, Jambi City, with their main livelihood being fish farming. This Village is a densely populated residential area and prone to flooding, with the main income of the community is still relatively low (around Rp. 1.500.00,-/month). Based on this condition, the implementation team invited the women to practice vegetables farming in the area around houses to meet the daily needs and even increase family income. The technology applied was vegetable cultivation by modifying hydroponic and verticulture techniques,  by utilizing water from fish ponds as a vegetable growing medium. Planting media containers use various plastic wastes which are often the main cause of river silting around settlements. This activity aims to improve farmers' knowledge and skills on environmentally friendly vegetable cultivation technology with hydroponic-verticulture techniques and inivited partners/farmers to have alternative farming businesses that can be an additional source of family income. The approach method used is participatory rural appraisal, which prioritizes the active participation of partners. The evaluation of activities showed an increase in participant's understanding and skills about the technology applied by more than 94%. The partnes looked very enthusiastic and ready to develop and design their own simple technology for vegetable farming around the house yard, to help the fulfillment of nutritional needs and increase family income.